2011
DOI: 10.1016/j.juro.2011.07.118
|View full text |Cite
|
Sign up to set email alerts
|

Animated Biofeedback: An Ideal Treatment for Children With Dysfunctional Elimination Syndrome

Abstract: Animated biofeedback effectively treats bowel and voiding dysfunction in children with dysfunctional voiding. Pelvic floor muscle exercises coordinate breathing and pelvic floor muscle contractions, and are beneficial in improving bowel dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 12 publications
0
45
0
3
Order By: Relevance
“…Furthermore, trials show a substantial lack of quality and harmonisation, resulting in heterogeneous treatment protocols and difficulties when interpreting the findings reported in the literature. Mixed results of BF treatment for constipation have been reported [24,54,57,59,60]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, trials show a substantial lack of quality and harmonisation, resulting in heterogeneous treatment protocols and difficulties when interpreting the findings reported in the literature. Mixed results of BF treatment for constipation have been reported [24,54,57,59,60]. …”
Section: Discussionmentioning
confidence: 99%
“…In those studies, patients were treated with biofeedback without stratification based on the mechanism responsible for the constipation (rectal pressure vs anal canal relaxation). Finally, more recent studies have now shown a long-term benefit to biofeedback in chronically constipated children (21)(22)(23). Additionally, some children received only 1 to 2 sessions of biofeedback (19).…”
Section: Discussionmentioning
confidence: 99%
“…7 Constipation was accurately evaluated, children with neurological abnormalities were excluded from analysis, and behavioral and physiological issues were not addressed.…”
mentioning
confidence: 99%
“…Kajbafzadeh et al used animated biofeedback (UrostymÔ) and measured pelvic floor activity along with abdominal muscle activity. 7 Six to 12 sessions were required. In the study by Klijn et al biofeedback was done in the patients' home and based on voiding.…”
mentioning
confidence: 99%